(3eSCdI ONhd hdO GdHfJ aj Gdehbha Ydi ChdGO GdChdGOs - (3CMeO Hf SdjeGf Hf ceGd HGTG GdQhej , TeS GdOjf,J (B940 (3g` s
(3ChdgG (B:s
(3hHYO aEf GdeSCdI GdSGjQI ai GdHdGO GdOGFQIeSCdI ONhd hdO GdHfJ s
(3BNQgG (B:s
(3aGdhjd dge hdef bdOge cd Gdhjd JeJ GdQSGdI s
(3Vef eLehY , JQJjHgG (B: (3GdKGfis
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B133 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B238 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B141s
(3eUOQ GbJfGA GdCUd (B:s
(3GdHdOjI HGdEScfOQjI (B(3791(3L(B) s
Keywords: (3GdHdGZIs